2022
DOI: 10.53682/eclue.v10i2.5213
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students` Reading Comprehension Through Collaborative Strategic Reading (Csr)

Abstract: The goal of this research was to examine whether or not Collaborative strategic reading (CSR) might increase students' reading comprehension. In this study, students struggled to understand narrative texts. Researchers used one class with pre-experimental design, and the sample consisted of 28 students of class X High School Swadharma Werdhi Agung. Multiple choice is a method of data collection. Before being given treatment, students were given a pre-test and after ended treatment, students were given post-tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The result of the study supports the findings of the previous works (Aghaie & Zhang, 2012;Bauer, 2022;Kusumawati &Widiati, 2017) suggesting that explicit vocabulary instruction is more effective in promoting students' reading comprehension skills. In addition, Moscho and Moscho (2017) conducted action research on the effects of explicit vocabulary instruction on reading comprehension, and the results indicated that explicit vocabulary instruction had an effect on improving students' reading comprehension skills.…”
Section: Pre-intervention Findings and The Analyses Of Reading Compre...supporting
confidence: 89%
“…The result of the study supports the findings of the previous works (Aghaie & Zhang, 2012;Bauer, 2022;Kusumawati &Widiati, 2017) suggesting that explicit vocabulary instruction is more effective in promoting students' reading comprehension skills. In addition, Moscho and Moscho (2017) conducted action research on the effects of explicit vocabulary instruction on reading comprehension, and the results indicated that explicit vocabulary instruction had an effect on improving students' reading comprehension skills.…”
Section: Pre-intervention Findings and The Analyses Of Reading Compre...supporting
confidence: 89%